Experiences of Burnout Syndrome and the Process of Recovery: A Qualitative Analysis of Narratives Published in Autobiographies - Krantz, Jaana; Eriksson, Madelen; Salzmann-Erikson, Martin (European Journal of Mental Health, 2021)
Burnout syndrome limits work capacity and the ability to manage a social and family life. Such limitations may lead to alienation from oneself and can result in frustration and anger. The recovery process may include a search for quick fixes from professionals but responsibility is in the hands of the ill with support from professionals, family, and work. Learning about limitations, the need to rest and accepting illness, are vital in the recovery process, but they are also associated with feelings of shame and blaming oneself for causing one’s own burnout by neglecting bodily signals. Objective: Burnout syndrome affects the individual as a whole because it involves emotional exhaustion, depersonalization, and a low sense of personal accomplishment. Research into burnout syndrome has predominantly focused on treatment outcomes measured using quantitative methods. The existing qualitative research has deepened theoretical insights from a lifeworld perspective, although, methodologically speaking, previous qualitative studies have been restricted to interviews. The qualitative interview method is somewhat limited. Hence, the objective of the present study was to analyze how autobiographers narrate their experiences of burnout syndrome and to describe their recovery process. Design: An inductive qualitative approach with a descriptive design was used to gain insights into the authors’ experience of burnout and recovery process, as expressed in writing. Setting/Subjects: The data comprised six autobiographies written by authors from Sweden. Results: The results are presented in three categories: 1) descriptions of estrangement from one’s own body, 2) descriptions of how the phenomenon is manifested in everyday life, and 3) descriptions of recovery processes. Conclusion: Burnout syndrome intersects both work life and family life and reveals the individual as a whole, integrated being. It is vital for healthcare professionals to adopt a person-centered approach that sees the individual as an integrated whole, consisting of body, mind, and soul.